Prevalence and distribution of psychological diagnoses and related frequency of consultations in Norwegian urban general practice - Mina Piiksi Dahli; Mette Brekke; Torleif Ruud; Ole Rikard Haavet (Taylor & Francis Group, 2020)
Objective: To investigate the prevalence and distribution of psychological diagnoses made by general practitioners (GPs) in urban general practice and the related frequency of consultations during 12 consecutive months in Norwegian general practice. Design: A cross-sectional study with data extracted from 16,845 electronic patient records in 35 urban GP practices Setting: Six GP group practices in Groruddalen, Norway. Subjects: All patients aged 16-65 with a registered contact with a GP during 12 months in 2015. Main outcome measures: Frequency and distribution of psychological diagnoses made by GPs, and the number of patients' consultations. Results: GPs made a psychological diagnosis in 18.8% of the patients. The main diagnostic categories were depression symptoms or disorder, acute stress reaction, anxiety symptoms or disorder and sleep disorder, accounting for 67.1% of all psychological diagnoses given. The mean number of consultations for all patients was 4.09 (95% CI: 4.03, 4.14). The mean number of consultations for patients with a psychological diagnosis was 6.40 (95% CI: 6.22, 6.58) compared to 3.55 (95% CI 3.50, 3.51) (p<0.01) for patients without such a diagnosis. Seven percent of the diagnostic variation was due to differences among GPs. Conclusions: Psychological diagnoses are frequent in urban general practice, but they are covered using rather few diagnostic categories. Patients with psychological diagnoses had a significantly higher mean number of GP consultations regardless of age and sex. Implications: The knowledge of the burden of psychological health problems in general practice must be strengthened to define evidence-based approaches for detecting, diagnosing and treating mental disorders in the general practice population.Key Points Eighteen percent of patients aged 16-65 in our study of patients in urban general practice received one or more psychological diagnoses in 12 months. Depression was the most common diagnosis; followed by acute stress reaction, anxiety and sleep disturbance. Patients with psychological diagnoses had a significantly higher mean number of consultations compared to patients without such diagnoses regardless of age and sex.